Localized amyloidosis of the ureter: A case report and literature review - Ding, Xiaobo; Wang, Yanbo; Yan, Xu; Wang, Chunxi; Wang, Yan (Canadian Urological Association Journal, 2013)
Localized amyloidosis of the ureter is a rare disease and can easily be confused with a neoplasm. We report the case of a 55-year-old woman who presented with loin pain and painless gross hematuria. We also reviewed the English literature about localized ureteral amyloidosis. Middle-aged women were likely to suffer from this disorder. Loin pain and hematuria were the main clinical features. There were no specific performance on radiologic imaging and ureteral calcification was not widespread. Compared to upper ureter and middle ureter, the lower ureter was the easiest involved part. Nephroureterectomy was the predominant treatment. Biopsies via a ureteroscope prior to surgery or intraoperative frozen section examination, which yielded the diagnosis of amyloidosis, could help to avoid unnecessary surgery. The use of dimethyl sulfoxide or follow-up with serial imaging may become a promising treatment.